Preparation and characterization of magnetic iron oxide nanoparticles functionalized by l-cysteine: Adsorption and desorption behavior for rare earth metal ions. Issue 3 (September 2016) - Ashour, Radwa M.; Abdel-Magied, Ahmed F.; Abdel-khalek, Ahmed A.; Helaly, O.S.; Ali, M.M.
Abstract: In this work, magnetic iron oxide nanoparticles functionalized with l -cysteine (Cys-Fe3 O4 NPs) was synthesized and fully characterized by transmission electron microscopy (TEM), X-ray powder diffraction (XRD), Fourier transform infra-red (FTIR), thermogravimetric analysis (TGA) and zeta potential measurements. The synthesized Cys-Fe3 O4 NPs has been evaluated as a highly adsorbent for the adsorption of a mixture of four rare earths RE 3+ ions (La 3+, Nd 3+, Gd 3+ and Y 3+ ) from digested monazite solutions. The influence of various factors on the adsorption efficiency such as, the contact time, sample pH, temperature, and concentration of the stripping solution were investigated. The results indicate that Cys-Fe3 O4 NPs achieve high removal efficiency 96.7, 99.3, 96.5 and 87% for La 3+, Nd 3+, Gd 3+ and Y 3+ ions, respectively, at pH = 6 within 15 min, and the adsorbent affinity for metal ions was found to be in order of Nd 3+  > La 3+  > Gd 3+  > Y 3+ ions. Using the Langmuir model, a maximum adsorption capacity of La 3+, Nd 3+, Gd 3+ and Y 3+ at room temperature was found to be 71.5, 145.5, 64.5 and 13.6 mg g −1, respectively. The Langmuir isotherm and pseudo-second order model fitted much better than the other isotherms and kinetic models. The obtained results for the thermodynamic parameters confirmed the spontaneous and endothermic nature of the process. Moreover, the desorption was carried out with 0.1 M nitric acid solutions. In addition, Cys-Fe3 O4 NPs can be used as a highly efficient adsorbent for the adsorption of La 3+, Nd 3+, Gd 3+ and Y 3+ ions from digested monazite solutions.